2015
DOI: 10.1242/jeb.114264
|View full text |Cite
|
Sign up to set email alerts
|

Sound pressure enhances the hearing sensitivity of Chaetodon butterflyfishes on noisy coral reefs

Abstract: Butterflyfishes are conspicuous members of coral reefs that communicate with acoustic signals during social interactions with mates and other conspecifics. Members of the genus Chaetodon have a laterophysic connection (LC) -a unique association of anterior swim bladder horns and the cranial lateral line -but the action of the LC system on auditory sensitivity is unexplored. Here, we show in baseline auditory evoked potential threshold experiments that Forcipiger flavissimus (which lacks swim bladder horns and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 57 publications
(77 reference statements)
0
18
0
Order By: Relevance
“…5). Previous studies have already measured behavioral audiograms in holocentrids (Tavolga and Wodinsky, 1963;Coombs and Popper, 1979), as well as AEP audiograms in a few pomacentrids (Egner and Mann, 2005;Wright et al, 2005;Wysocki et al, 2009) and chaetodontids (Webb et al, 2012;Tricas and Boyle, 2015). However, direct comparison of these studies with our AEP traces can be irrelevant because audiograms produce very different results depending on the methodology used (i.e.…”
Section: Interspecific Differences In Auditory Capabilitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…5). Previous studies have already measured behavioral audiograms in holocentrids (Tavolga and Wodinsky, 1963;Coombs and Popper, 1979), as well as AEP audiograms in a few pomacentrids (Egner and Mann, 2005;Wright et al, 2005;Wysocki et al, 2009) and chaetodontids (Webb et al, 2012;Tricas and Boyle, 2015). However, direct comparison of these studies with our AEP traces can be irrelevant because audiograms produce very different results depending on the methodology used (i.e.…”
Section: Interspecific Differences In Auditory Capabilitiesmentioning
confidence: 99%
“…During each trial, 14 different frequencies were presented: 150, 300, 600, 900, 1200, 1500, 1800, 2100, 2400, 2700, 3000, 3300, 3600 and 3900 Hz; these frequencies covered the expected range of hearing of the studied species (e.g. Coombs and Popper, 1979;Egner and Mann, 2005;Tricas and Boyle, 2015). Sound levels at each frequency were presented at up to 162 dB rms re 1 μPa and were attenuated in 6 dB steps until a threshold level was determined.…”
Section: Stimulus Generation and Aep Recordingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the pressure-mediated mode of fish hearing requires the use of specialized morphological adaptations that enable fish to transduce the pressure-induced vibrations of the swim bladder to the otolithic end organs to detect sound pressure. Otophysan fish, such as the goldfish (Carassius auratus) and zebrafish (Danio rerio), possess skeletal adaptations known as Weberian ossicles that link the swim bladder to the inner ear for enhanced pressure detection while other fishes such the Hawaiian squirrelfish (Myripristis kuntee) and the West African ladyfish (Elops lacerta) have no specialized connections between the swim bladder and inner ear, but do exhibit increased pressure sensitivity simply due to the close proximity of these gas-filled structures to the inner ear (Greenwood 1970;Coombs and Popper 1979;Braun and Grande 2008;Tricas and Boyle 2015). Additional studies have shown that natural or artificial gasfilled bladders without direct apposition to the inner ear can also significantly enhance hearing sensitivity in fishes (Chapman and Sand 1974;Jerko et al 1989).…”
Section: Appropriate Stimulimentioning
confidence: 99%